AB1347 Influence of low socioeconomic status on autoimmune rheumatic diseases. (23rd January 2014) - Anaya, J.M.; Amaya-Amaya, J.; Amador-Patarroyo, M.J.; Herrera-Diaz, C.; Quintero, O.L.; Cardenas-Roldan, J.; Giraldo-Villamil, J.; Barragan-Ardila, C.; Caro-Moreno, J.; De-San-Vicente, Z.; Cruz-Tapias, P.; Rodriguez-Rodriguez, A.; et al.
Abstract : Objectives: To analyze the influence of socioeconomic status (SES) on the course of autoimmune rheumatic diseases (AIRD) in an admixed and socio demographic heterogeneous population. Methods: This was a cross-sectional analytical study in which 1096 consecutive patients with rheumatoid arthritis (RA, n=678), systemic lupus erythematosus (SLE, n=258), and Sjögren syndrome (SS, n=160) were included. SES was categorized according to the national legislation and was dichotomized as high (status 3 to 6) and low SES (status 1 and 2).Sociodemographic, clinical and laboratories variables were collected by means of a structured interview and a medical record review.Bivariate and logistic regression analyses were performed for each population sample. Results: Significant association between low SES and a stronger autoimmune response was observed (Table). In addition, low SES influences the presence of arthritis, Raynaud's phenomenon, and discoid lupus in SLE. As expected, an association between low SES and low educational level was observed in SLE and SS, while in RA a low SES was also associated with housewives. Conclusions: Our results indicate that SES influences the clinical presentation of AIRD. These results could be related to the admixture of our population, environmental factors, and the quality of health insurance, and deservefurther research. Also, the results might help to define public health policies in order to improve AIRD outcome in low SES patients. Disclosure of Interest: None Declared